Circulating Plasma microRNA to Differentiate Cushing's Disease From Ectopic ACTH Syndrome - Belaya, Zhanna; Khandaeva, Patimat; Nonn, Larisa; Nikitin, Alexey; Solodovnikov, Alexander; Sitkin, Ivan; Grigoriev, Andrey; Pikunov, Mikhail; Lapshina, Anastasia; Rozhinskaya, Liudmila; Melnichenko, Galina; Dedov, Ivan (Frontiers in Endocrinology, 2020)
Corticotropinomas and adrenocorticotropic hormone (ACTH)-secreting neuroendocrine tumors exhibit differential levels of some microRNAs (miRs) compared to normal tissue. Because miRs can be released from tissues into circulation, they offer promise as novel disease biomarkers. Objective: To evaluate whether miRs are differentially detected in plasma samples of patients with ACTH-dependent Cushing’s syndrome (CS) Design: Case-control study Methods: Morning fasting plasma samples were collected from 41 consecutive patients with confirmed ACTH-dependent CS and 11 healthy subjects and stored at −80°C. Twenty-three miRs previously reported to be differentially expressed in ACTH-secreting tumors versus healthy tissue samples were quantified in plasma by qPCR. Results: Among enrolled subjects, 28 were confirmed to have Cushing’s disease (CD), 13 had ectopic ACTH secretion (EAS) and 11 were healthy controls. We found statistically significant differences in the circulating levels of miR-16-5p [45.04 (95% CI 28.77–61.31) in CD vs. 5.26 (2.65–7.87) in EAS, P<0.001; q=0.001], miR-145-5p [0.097 (0.027–0.167) in CD vs. undetectable levels in EAS, P=0.008; q=0.087] and differences in miR-7g-5p [1.842 (1.283–2.400) in CD vs. 0.847 (0.187–1.507) in EAS, P=0.02; q=0.14]. The area under the receiver-operator (ROC) curve was 0.879 (95% CI 0.770-0.987), p< 0.001, when using miR-16-5p to distinguish between CD and EAS. Circulating levels of miR-16-5p in the healthy control group differed from that of both the CD and EAS groups. Conclusions: Plasma miR levels differ in patients with CD and EAS. In particular, miR-16-5p, miR-145-5p and miR-7g-5p are promising biomarkers for further research to differentiate ACTH-dependent CS.